Long non-coding RNA LINC00858 promotes cells proliferation, migration and invasion by acting as a ceRNA of miR-22-3p in colorectal cancer - Qian-Kun Sha; Lin Chen; Jia-Zhuang Xi; Hang Song (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Though long non-coding RNA LINC00858 (LINC00858) has been shown to be involved in tumours of other tissues, its involvement in colorectal cancer (CRC) is still unknown. We aimed to investigated expression and mechanism LINC00858 in human CRC. In this study, we firstly found that LINC00858 expression was significantly up-regulated in both CRC tissues and cell lines by both online data and RT-PCR assay. Then, clinical assay revealed that high LINC00858 expression was significantly associated with advanced clinical progression and poor prognosis. Multivariate analysis demonstrated that high LINC00858 expression was an independent poor prognostic factor for CRC patients. Moreover, lost-of-function assay indicated that knockdown of LINC00858 suppressed CRC cells proliferation, migration and invasion, and promoted apoptosis. Mechanistically, bioinformatics analysis, dual-luciferase reporter assays, and western blot assays showed that LINC00858 functioned as competing endogenous RNA to repress miR-22-3p, which controlled its down-stream target YWHAZ. Then, we suggested that LINC00858 exerted its function through the miR-22-3p/YWHAZ axis. To our knowledge, this is the first report which showed the role of LINC00858 in the progression of CRC. Our findings indicated that LINC00858 played an important role in CRC, and may serve as a novel prognostic factor and therapeutic target.